Rancang bangun wiring dan program untuk sistem kendali pada motor stepper - Jibril, Rosyidin; Wardoyo, Adik Susilo (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
PT AWW operates several plants, one of which is a mixing plant that produces compounds. The mixing plant produces two types of compounds: master-batch compounds and final-batch compounds. Master-batch compounds are not allowed to undergo the metal detector process.  In contrast, final-batch compounds are reprocessed master-batch compounds with the addition of final-batch powder, making them suitable for the Metal Detector process. The processed final-batch compounds pass through the metal detector machine for foreign material detection. However, a problem was identified during the process: operators are required to manually mark compounds with foreign material, resulting in loss time. This loss time occurs when the machine detects foreign material in the compounds, and operators need time to mark the detected compounds. Therefore, a marking tool was developed to facilitate operators in marking compounds detected with foreign material. Design and construct wiring and programming for a control system utilizing a stepper motor as the actuator for a marking tool based on Arduino Mega and TB6600 driver, resulting in a semi-automated tool. This eliminates the need for manual marking and replaces it with a one-button operation marking device..